Optimalisasi Pencegahan Osteoporosis Melalui Pemeriksaan Kalsium Pada Wanita Subur Dan Wanita Menopause Di Kelurahan Kemantren Cirebon - Muhammad Ibnu Ubaidillah; Misika Alam; Solikhah Solikhah; Pipin Supenah; Hery Prambudi; Rizal Ibrahim Aji; Nadila Nur Rahmaliani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Maintaining a balance of calcium levels at a young age is proportional to the high or low risk of developing bone mass loss disease. More than 30% of menopausal women over the age of 50 are at risk of developing osteoporosis due to low calcium levels. Decreased bone mass due to low calcium levels can affect anyone, including women of childbearing age. In fertile women who are still producing the hormone estrogen when entering the menstrual phase, especially before menstruation, calcium levels can decrease. Although it is still in the normal range, calcium itself can have an effect, one of which brings symptoms that lead to a calcium deficiency condition. This activity aims to determine blood calcium levels in women of childbearing age and in menopausal women so that osteoporosis can be prevented in Kemantren Village, Cirebon Regency. The method of this activity is by conducting observations, interviews and blood calcium examinations. The results of the activity were carried out on 30 samples of women of childbearing age and 30 samples of menopausal women from Kemantren Village, Cirebon Regency. The average value of blood calcium levels in women of childbearing age was 8.83 mg/dL with the highest and lowest blood calcium levels of 10.80 mg/dL and 6.67 mg/dL, respectively. The conclusion of this activity is that fertile and menopausal women are known to have normal calcium levels.